Modelagem Matemática na formação inicial de pedagogos - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Mathematical Modeling in Mathematical Education perspective has been pointed out on Basic Education scope, as a change about the in force educational practices, corresponding the most dynamic, attractive and establishment actions, related to Mathematics and daily routine from the students. Its insertion in the school’s context has caused in Mathematical Education community meaningful discussions and movements for this methodology take part in the spaces for teacher’s training or even that sets in a formative model. On this context, it is understood that practices with Mathematical Modeling, despite of being early, are present in childhood, pedagogue’s initial education, as educators of this cycle, also deserves attention and, that’s why it was implemented/encouraged the contact with Mathematical Modeling in Pedagogy graduation course, which the academics, established learning with/about Mathematical Modeling in outreach academics (outreach programs), researches and internship. From the academic’s experience emerged the following questioning: What does it show in discourse from academics, about Mathematical Modeling on initial academic education of pedagogues? This, therefore, admitted as research questioning was persecuted under phenomenological attitude, which was directed to theoretical studies about Mathematical Modeling in Education perspective, on academic education of pedagogues and Mathematics teaching and as main aspect of the research, understood the identification of discourses/perceptions of academics about Mathematical Modeling in its initial process. About the collected discourses, the interviews with audio recording were transcript and afterwards, treated with software aid named Atlas.ti in an interpretative phenomenological hermeneutics action that allowed the identification of 5 (five) categories: C1) Memories about Mathematics and its teaching presented from Mathematical Modeling; C2) Justifications for living, researching, and using Mathematical Modeling; C3) Assigned meanings to Mathematical Modeling; C4) Built knowledge or mobilized through Mathematical Modeling; and C5) Consequences and repercussions of practices with Mathematical Modeling. These, it is possible to interpret that Mathematical Modeling, forwarded by the conception and steps by Burak (1992; 2004; 2010), it is constituted in a methodology of academic education for pedagogues, childhood educators, that create opportunity for development of teacher knowledge, as research, reflection, dialogue, cooperation, specific content learning, on interdisciplinary approaching and, mainly the redetermination of teaching Mathematics and education practices in childhood.
Keywords: Educação Matemática; Formação de professores; Modelagem Matemática; Pedagogia; Mathematical Education; Teacher’s Academic Education; Mathematical Modeling; Pedagogy; CNPQ::CIENCIAS HUMANAS::EDUCACAO